ACE I/D gene polymorphism in athletes of various sports disciplines - Holdys, J.; Krysciak, J.; Stanislawski, D.; Gronek, P. (Human Movement, 2011)
Genetic factors play an important role in physical performance. In this study, the polymorphism of the angiotensin-converting enzyme gene (ACE) was analyzed in relation to the level of physical fitness, measured by maximal oxygen uptake (VO2max). Methods. Molecular genetic research on the ACE gene was carried out on a group of 154 men and 85 women. All of the subjects were Polish students at the University School of Physical Education in Poznan' and included professional athletes representing various sport disciplines and levels of fitness. Results. Allele I was found to have an advantageous effect on higher maximal oxygen uptake values and, in addition, a characteristic distribution of genotypes was found, where allele II was more common in individuals practicing aerobic sports and allele DD in individuals training anaerobic disciplines. Conclusion. No significant associations were found between I/D polymorphism in the ACE gene and VO2max values but certain tendencies were found for those individuals with the ACE II genotype.